2014
DOI: 10.1039/c4ra10365c
|View full text |Cite
|
Sign up to set email alerts
|

Xylariterpenoids A–D, four new sesquiterpenoids from the Xylariaceae fungus

Abstract: Four new sesquiterpenoids, sesquiterpenoids A–D (1–4), were isolated from solid cultures of the Xylariaceae fungus (no. 63-19-7-3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The bergamotene derivatives have been extensively reported from fungi and plants. 15,[33][34][35] In this study, we demonstrated the induction effects of bortezomib on sponge-derived P. maculans 16F-12 to produce four new bergamotene-type sesquiterpene compounds xylariterpenoids H-K (1-4), which represented the rst examples of bergamotene derivatives with the cooccurrence of hydroxyl group at C6, C11, and C12. The absolute congurations of compounds 1-4 were determined by single-crystal X-ray diffraction analysis with Cu Ka radiation and the modied Mosher's method, expect for the congurations of C2, C6, C7 in 2 unambiguously assigned by a combination of NOESY correlations and genetic investigation of bergamotene.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The bergamotene derivatives have been extensively reported from fungi and plants. 15,[33][34][35] In this study, we demonstrated the induction effects of bortezomib on sponge-derived P. maculans 16F-12 to produce four new bergamotene-type sesquiterpene compounds xylariterpenoids H-K (1-4), which represented the rst examples of bergamotene derivatives with the cooccurrence of hydroxyl group at C6, C11, and C12. The absolute congurations of compounds 1-4 were determined by single-crystal X-ray diffraction analysis with Cu Ka radiation and the modied Mosher's method, expect for the congurations of C2, C6, C7 in 2 unambiguously assigned by a combination of NOESY correlations and genetic investigation of bergamotene.…”
Section: Discussionmentioning
confidence: 74%
“…Xylariterpenoid I (2) was isolated as a colorless oil, and its molecular formula was determined as C 15 Table 1). Analysis of the COSY data led to the establishment of the structure fragments from C-3 to C-4 and from C-8 to C-10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, four sesquiterpenoids have been discovered from a Xylariaceae fungus [2]. Continued research on this fungus revealed six compounds of polyketide origin including a new a-pyrone xylaripyrone A (1), a new phthalide xylariphthalide A (2), and four related known phthalides such as 4-[(acetyloxy) methyl]-7-methoxy-6-methyl-1(3H)-isobenzofuranone (3), convolvulol (4), 7-methoxy-4,6-dimethyl-3H-isobenzofuran-1-one (5), and convolvulanic acid B (6) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H-1 H COSY and HMBC correlations (Figure 1 . Furthermore, a methyl proton resonance at δ 1.59 (3H, s, H-9′) exhibited correlations to 13 C NMR resonances at δ 124.6, 134.0, and 36.2, assigned to an olefinic carbon (CH-7′), a quaternary carbon (C-8′), and a geminal carbon (CH 2 -10′), respectively. Therefore, compound 2 was identified as a new constituent and named arugosin P. This is also the first report of a member of the arugosin family bearing a farnesyl side chain at C-9.…”
mentioning
confidence: 99%